Progress and prospects of international carbon peaking and carbon neutral research –based on bibliometric analysis (1991–2022) - Zheng, Ye; Li, Zhenmiao; Chai, Jinlai (Frontiers in Energy Research, 2023)
Carbon peak and carbon neutrality is an important strategic measure to tackle climate change and is of great significance to global climate governance, human development, and scientific and technological progress. In this paper, we used 3,824 papers in the core collection of Web of Science from 1991 to 2022 as a sample, and used bibliometric analysis and CiteSpace, a visual knowledge network analysis tool, to sort out the current status of international carbon peak and carbon neutrality research in terms of publication trends, temporal distribution, spatial distribution, keyword co-occurrence mapping, and research basis. And then the current hot topics of research are explored,including carbon neutralization technology, climate policy impact and performance evaluation, carbon pricing and carbon finance, citizen participation attitude and behavior, and climate governance and global cooperation. Research prospects have been presented in terms of four aspects: building the integrated research framework of carbon peak and carbon neutral research, establishing a comprehensive and efficient environmental policy system, expanding research cooperation, deepening research and application of carbon peak carbon-neutral technology.